Efficient and Effective Asset Management System of Medical Imaging Equipment : Key Challenges and Enablers - Tran, Huyen (My University, 2024)
Medical imaging diagnostic plays a critical role in healthcare. It enables healthcare practitioners to have accurate diagnostics, treat and monitor a large range of health conditions and significantly contribute to improving outcomes for patients. However, the effective management and control of medical imaging equipment poses some challenges for healthcare organizations in meeting asset management objectives, including operational efficiency, optimal life cycle management, risk management, and cost effectiveness. Therefore, the phenomenon of interest of this research is the inefficient asset management system of medical imaging equipment. It is crucial for healthcare organizations to understand why asset management system (AMS) of medical imaging equipment (MIE) may not achieve asset management objectives. The primary purposes of this study were to gain an in-depth understanding of the current asset management practices for MIE within the case company, identify the key challenges and enablers for implementing an effective and efficient AMS and finally provide theoretical and managerial implications for AMS in the healthcare sector. The main research question of this study is "Why can asset management systems fail to be as efficient and effective as intended?" To answer this question, the author decided to seek for the answers for the following sub questions:" How is asset management system managed within an organization?", " What are the key challenges that an organization can encounter in implementing an asset management system?” and “What are the key enablers to an effective and efficient asset management system?”. The answer to the above questions will be discovered through the research process which incorporates a thorough analysis of the extant literature and further complemented by empirical findings. This research adopted the qualitative method with a single case study strategy. Data collection was done through semi-structure interviews with 16 participants from different stakeholder groups, secondary data was collected through direct observation, platform, report and document analysis. Thematic analysis method was employed for data analysis to identify patterns and themes related to AMS. The empirical findings revealed some significant gaps in the AMS for MIE at the case company which includes asset management perception as not a strategic priority which results inadequate leadership and support, data integrity issues, inefficient AIS, lack of control for outsourced processes during lifecycle management and risk management. This study has contributed to the body of knowledge for asset management by demonstrating that the application the ISO 55001:2014 AMS framework in assessing asset management practices, developing, improving and maintaining AMS can be beneficial for organizations within the healthcare sector. Furthermore, an enabling framework to guide the effective implementation of AMS was developed and the researcher also emphasizes the significance of organizational readiness as a critical factor for AMS implementation. Therefore, this study offers valuable insights into the theoretical and practical aspects of AMS for MIE in the healthcare sector. It also identified some future research opportunities with the potential to contribute further to AM academic research.
Keywords: Asset Management, Medical Imaging Equipment Asset Management, Asset management system